Pandemic influenza: preparing for an uncertain inevitability. - Kenneth A McLean (Inishmore Laser Scientific Publishing Ltd, 2017)
When it comes to pandemic influenza, the question is not "if", but "when" this will occur. There has been substantial progress from the GAP over the past 10 years, and the world is more prepared than ever for an influenza pandemic. Nonetheless, there remain significant challenges to ensure there is sufficient and timely vaccine production and distribution to effectively respond when the next emerges. Zika, Ebola, Middle-Eastern Respiratory Syndrome (MERS), Severe Acute Respiratory Syndrome (SARS) - these viruses have dominated headlines in recent decades as potential pandemic threats. We cannot know what the next outbreak will be, however the most enduring and inevitable risk remains that of a pandemic influenza outbreak. While there are possible pandemic candidates like Avian (H5N1) or Swine flu (H1N1), these remain difficult to predict. The influenza virus is highly mutable, rapidly evolving to alter the antigens displayed to present a novel challenge to the immune system. It is this feature that poses the pandemic risk, and also that ensures it is inherently difficult to produce a 'universal' vaccine. Each year, the World Health Organisation (WHO) must produce recommendations for influenza subtypes to include within the seasonal vaccine, based on predictions from global surveillance activities. Therefore, the capability to rapidly institute a global vaccination programme remains paramount to provide effective protection of the world population.